Marketing strategy plan for hospital X in east Jakarta during the Covid-19 pandemic - Hijriani, Hijriani; Achadi, Anhari (Gema Wiralodra, 2023)
The hospital marketing strategy plan is a set of strategies that the hospital can use as a hospital management and development guideline. It is essential to plan a marketing strategy in dealing with the COVID-19 pandemic during this pandemic. The East Jakarta Health Office appointed Hospital X in East Jakarta to become a referral hospital for COVID-19. This study aims to determine the marketing strategy plans used by hospitals during the COVID-19 pandemic. The method used in this study uses a descriptive-analytic design through observation, structured interviews, and using secondary data. Analysis of the research data used qualitative analysis, which consisted of data collection, reduction, and verification/conclusion data presentation. The research findings show that the marketing strategy plan carried out by X Hospital in East Jakarta during the COVID-19 pandemic is to increase information technology advances, namely by marketing superior services through digitalization. In addition, marketing is also focused on increasing COVID-19 patients by making specific promos.